Review of the Deformation Mechanism and Earth Pressure Research on the Double-Row Pile Support Structure - Zhou, Yijun; Luo, Liangrui; Zheng, Linxue (Frontiers in Earth Science, 2022)
As a new support structure system, double-row pile is widely used in foundation pit engineering, slope engineering, water conservancy engineering and other fields.It has a big horizontal stiffness and strong anti-overturning ability, and has less impact on the surrounding neighboring existing buildings (structures) when it is applied.It must be mentioned that the design experience of double-row pile is ahead of the theory, some research has been carried out on double-row pile support structure. This work reviews and evaluate the force deformation and earth pressure on piles of double-row pile,including pile deformation damage mechanism, soil pressure distribution law and double-row pile structure form.In addition, the problems and shortcomings of the current double-row pile research are concluded.These results have enriched the study of the mechanism of double-row piles, provided the theoretical guidance for double-row pile support structures, and laid the foundation for further theoretical research.